Alterations in the acoustic production of odontocetes across co-occurrence contexts - Pinto, Yasmin Viana (Universidade Federal de Juiz de Fora (UFJF), 2023)
Co-occurrence contexts among odontocetes – Parvorder Odontoceti, Infraorder Cetacea - have been reported by many scientists, yet, the implications of these coexistences in the acoustic space remain unclear. Once odontocetes rely on acoustic signals to forage, navigate and for social communication, understanding if species alter the use and structure of acoustic signals among the diverse cetacean co-occurrence contexts may enhance a better comprehension of the acoustic role on species identification, behavior, and ecological interactions. In order to evaluate the acoustic role and assess whether acoustic structures are affected within these interactions, this thesis was organized in three chapters: The first chapter consists on a literature review on different co-occurrence contexts under the acoustics perspective across cetacean species, focusing on odontocetes, and discussing the strategies, specially the acoustic strategies, employed by these species among different interactions. Chapter two and three used data collected in the Western South Atlantic Ocean through a towed array of hydrophones to evaluate acoustic structure among mixed-species groups (MSGs) compared to single-species groups (SSGs). Chapter one used whistles to investigate the acoustic relationships of Tursiops truncatus when involved in different group contexts: in MSGs with two other delphinid species and in SSG. Acoustic recordings of T. truncatus single species groups and in associations with Globicephala melas and Grampus griseus were collected. In order to verify the differences among whistles produced in such contexts a support vector machine and random forest analysis were implemented. Both analyses revealed a clear separation of whistles from the SSGs versus the MSGs as well as between both MSGs. The results indicate that interspecific associations may influence the whistle structure and suggest that T. truncatus whistles can be modified during interspecific interactions. Chapter three aimed to evaluate the acoustic role and possible ...